Exploring Urinary Heparin-Binding Protein as a Diagnostic Biomarker for Asymptomatic Bacteriuria in Gestational Diabetes Mellitus: Bridging Microbial Insights and Clinical Innovations - Adiga, Sachidananda; Vasishta, Sampara (Journal of Neonatal Surgery, 2025)
Background: There is a high frequency of asymptomatic bacteriuria (ASB) during pregnancy among females. GDM is a strong risk factor for ASB development during the course of pregnancy because it leads to impairment of immune status and provides a favorable environment for the growth of bacteria. In this investigation, the aim was to determine the levels of urinary heparin-binding protein (UHBP) in GDM and non-GDM groups, examine the urinary heparin-binding protein levels in GDM pregnant women and the diagnostic value of UHBP for evaluation of ASB. Methods: This was a case control study with a total of 160 participants including 80 pregnant women diagnosed with gestational diabetes mellitus and 80 healthy pregnant women. All participants were subjected to routine urine culture and microbiological tests, as well as assessment for UHBP levels. For continuous variables, Mann-Whitney U test was used and for categorical variables, Fisher’s exact test was conducted. The sensitivity and specificity of UHBP for diagnosis of culture proven cases of ASB was done using ROC curves. Results: The levels of UHBP were notably diminished in the GDM mothers as compared to the controls (p=0.0116). During ROC curve evaluation, however, UHBP for ASB was found to be of limited diagnostic value since the area under the curve (AUC) was 0.370 for the GDM and 0.519 for the normal group. This indicates that UHBP is not a good single diagnostic marker. Conclusion: This study underscores the potential impact of asymptomatic bacteriuria (ASB) in gestational diabetes mellitus (GDM) on neonatal health. Neonates born to mothers with GDM and ASB may face heightened risks of infections and other complications due to maternal immune dysregulation. The findings stress the importance of maternal screening to improve neonatal outcomes by mitigating risks of preterm birth and low birth weight associated with untreated ASB.